Persons tried, New South Wales 1788-1810 - Roberts, David Andrew (ADA Dataverse, 2019)
Trials in Court of Criminal Jurisdiction NSW 1788-1810. The data includes name, offence, trial date, verdict (where known), sentence, number of co-accused and name and sex of victim or complainant (where known)